2018
DOI: 10.3389/fneur.2018.00978
|View full text |Cite
|
Sign up to set email alerts
|

Microglia in Alzheimer's Disease: Risk Factors and Inflammation

Abstract: Microglia are resident immune cells in the central nervous system (CNS) that originate from myeloid progenitor cells in the embryonic yolk sac and are maintained independently of circulating monocytes throughout life. In the healthy state, microglia are highly dynamic and control the environment by rapidly extending and retracting their processes. When the CNS is inflamed, microglia can give rise to macrophages, but the regulatory mechanisms underlying this process have not been fully elucidated. Recent geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(79 citation statements)
references
References 82 publications
0
79
0
Order By: Relevance
“…Many transcriptomic analyses have shown that there are significant upregulation of immune response genes and downregulation of neuronal function genes in AD (Miller et al, 2008;Zhang et al, 2013). It is widely accepted that microglia clusters near amyloid plaques and microgliamediated inflammation are activated in in the progression of AD (Clayton et al, 2017;Hansen et al, 2018;Katsumoto et al, 2018). However, most of such studies used bulk brain samples containing mixed cell types without taking microglia cell abundance change into account.…”
Section: Discussionmentioning
confidence: 99%
“…Many transcriptomic analyses have shown that there are significant upregulation of immune response genes and downregulation of neuronal function genes in AD (Miller et al, 2008;Zhang et al, 2013). It is widely accepted that microglia clusters near amyloid plaques and microgliamediated inflammation are activated in in the progression of AD (Clayton et al, 2017;Hansen et al, 2018;Katsumoto et al, 2018). However, most of such studies used bulk brain samples containing mixed cell types without taking microglia cell abundance change into account.…”
Section: Discussionmentioning
confidence: 99%
“…The studies conducted on postmortem brain tissues have revealed excessive chronic inflammation in the plaque area. A key phenomenon underlying AD-related neuroinflammation is the proliferation and accumulation of microglial cells around plaques, which results in the expression of pro-inflammatory cytokines and chemokines as well as neuronal cell death (42)(43)(44).…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…In the case of AD, these microglial cells of the brain assem-ble around the neurons but are not successful in performing their function of clearing the debris. Thus, their build-up results in the release of chemicals that lead to chronic inflammation in the brain [10]. 5.…”
Section: Formation Of A␤ Plaques Formation Of A␤ Pro-mentioning
confidence: 99%